O quarto excluído: gêneros não binários e formação universitária - Góes, Fernanda Karla Fernandes Da Silva (2019)
In the 21st Century, plural genders spectrium make up identities, bodies, sexualities and narratives that, in the face of their performances and acts of gendramatics, often express antagonistic behaviors to the prescriptions of falocentrism (mark of power of male superiority), patriarchy (male authority), heteronormativity (power device imposed as the only valid sexual identity), heterosexualism (ideological system that legitimizes heterosexuality as a standard) and heterosexual contract (subjection of the other to standardized gender roles), among other factors.This time, in contemporaneity, there is a revolution of customs unprecedented in relation to diversity/gender differences, whose resistance and historical confrontation guided public policies and rights conquests, especially in recent decades. Therefore, this research aims to understand gender non-binarity in learning contexts in university education. In methodological terms, it is a field research, a qualiquantitative approach, an exploratory type. The universe was constituted by the Higher Education Institute of Paraíba (IESP), which structure higher education from three areas of knowledge: Health Sciences, Exact and Technological Sciences, and Humanities. The sample was non-probabilistic, whose sample criterion was random (draw), and selected two/teachers by area (six in all). He also selected as an intentional sample, two/two students per area (six in all), these/the last/as expressing non-binary gender performances. The research availed of the perspective of organization of categories as a way of systematization and interpretation of results, whose strategy was given from the method of the room “excluded”, from situations-problem guided by the choice of images as answers. In the results, emerged categories like “outside the standard”, “pattern break”, “gender inequality”, “minority”, “nuisance”, “different”, among other nuances, who emphasized the reasons why teachers and students perceive the socio-cultural subjugations to which non-binary university students are victimized/their daily lives. The teachers/teachers recognize the pedagogical and institutional unpreparedness to deal with non-binary people in the classroom. For going beyond the boundaries of the compositions established between being a man and being a woman, through their performance acts, non-binary students feel the force of the normative impositions that tarnish on themselves/as the dominance of the sex-gender system, which implies to say that the (re)construction of the subject is a constant struggle that resists the forms of reification, authoritarianism, indifference, disrespect and symbolic violence with which they are subjected/as in the classroom and other institutional spaces. With this, the research finds how non-binary students are, in fact, the most excluded people in learning contexts of university education, in the IESP. Therefore, the supremacy of binary discourse (heteronormative) invades the university scene through the control of the body and behavior, which brings contradictions to the formative process itself and to the goals of the IES. This requires intervention actions, through planned and consistent institutional policies, that favor the conditions of learning regardless of gender condition.